ANALISIS PESAN DAKWAH VIDEO “JANGAN ADA DENDAM DAN KEBENCIAN KEPADA SIAPAPUN” PADA AKUN YOUTUBE KH. BUYA SYAKUR YASIN, M.A - Ali Sobirin; Muhammad Nur Kholis AR (Melati Institute, 2022)
YouTube is part of the internet. Everyone can use this media to do their da'wah, like Buya Syakur. The content that YouTube users are interested in is